Formulation of synbiotic buttermilk powder with higher viability of probiotic cells - Anu Ahlawat; Harsh B. Jadhav; Laxmi Ananthanarayan (Food Chemistry Advances)
The present study focused on the use of trehalose (TRE), whey protein concentrate (WPC), pullulan (PUL), and calcium lactate gluconate (CAL) as a protectant in the formulation of synbiotic buttermilk powder by application of spray drying. The spray drying of the solution mixture was carried out at an inlet temperature of 150 °C, a feed flow rate of 15mL/min, and compressed air at 3 kg/cm2 while keeping the outlet temperature constant at 70 ± 5 °C. TRE4 + CAL0.5 showed good results with the viability of Bifidobacterium bifidum as 6.04 ± 0.13 after 16 weeks followed by TRE2 + CAL0.5, TRE4, CAL0.5, WPC6, PUL4, and Control. The addition of protectants and Fructooligosaccharide (FOS) as a prebiotic did not affect the powder properties. The moisture content, water activity, bulk density, hygroscopicity, solubility, particle size, and scanning electron microscopy (SEM) of SBMP were better than the control sample for 17 weeks. SEM results showed spherical shapes without any cracks for SBMP containing TRE4 + CAL0.5. The present work demonstrated that the formulation containing TRE4 + CAL0.5 showed excellent results in terms of the viability of probiotic cells and also physicochemical properties of powder during storage for 16 weeks at 4 ± 1 °C.